2023
DOI: 10.3389/fnut.2023.1114053
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index and prognosis of patients with coronary artery disease: A systematic review and meta-analysis

Abstract: BackgroundThis review assessed if prognostic nutritional index (PNI) can predict mortality and major adverse cardiac events (MACE) in coronary artery disease (CAD) patients.MethodsPubMed, Web of Science, Scopus, and Embase were searched up to 1st November 2022 for all types of studies reporting adjusted associations between PNI and mortality or MACE in CAD patients. A random-effect meta-analysis was conducted for PNI as categorical or continuous variable. Subgroup analysis were conducted for multiple confounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The PNI is a reliable indicator of the immunonutritional status of individuals, which is based on lymphocyte and albumin levels. Recent findings have not only substantiated the potential of the PNI as a prognostic indicator for various malignancies (19)(20)(21)(22), COVID-19 (9,23), coronary artery disease (24), and acute renal dysfunction (25), but also shown that a lower PNI has been linked to increased mortality risk in elderly individuals with CKD (26), and diabetic kidney disease (DKD) (27). In this study, we further corroborated the significant correlation between the PNI and CKD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The PNI is a reliable indicator of the immunonutritional status of individuals, which is based on lymphocyte and albumin levels. Recent findings have not only substantiated the potential of the PNI as a prognostic indicator for various malignancies (19)(20)(21)(22), COVID-19 (9,23), coronary artery disease (24), and acute renal dysfunction (25), but also shown that a lower PNI has been linked to increased mortality risk in elderly individuals with CKD (26), and diabetic kidney disease (DKD) (27). In this study, we further corroborated the significant correlation between the PNI and CKD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have found that malnutrition was closely associated with poor prognosis in patients with cardiovascular disease ( 20 22 ). Data from Europe and the Americas showed that up to one-third of hospitalized patients were at risk of malnutrition or were malnourished upon admission, especially in acutely ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation was a key mediator on the impact of malnutrition for the prognosis of cardiovascular disease 3 . In recent years, many studies have showed that PNI was an adverse predictor in cardiovascular disease 4,5 . Prognostic nutritional index (PNI) was calculated from serum albumin levels and absolute lymphocyte counts, which was a comprehensive index re ected not only protein stores but also the immunological status.…”
Section: Introductionmentioning
confidence: 99%